DISTRIBUTION AND IMPORT OF PLANT PROTECTION PRODUCTS AND PLANT NUTRITION PRODUCTS IN REPUBLIC OF SERBIA - Dabović, Dušan (Economics of Agriculture, 2011)
In mid-2009 the Republic of Serbia adopted the Law on plant protection products (pesticides) and the Law on plant nutrition products (fertilizers), which are in accordance with relevant international legislation, particularly with the regulations and directives of the European Union. In this way, these laws created the basis for establishing a modern system in the area, which will be finished after the adoption of rules on specific technical issues. The new legal framework has made changes regarding liberalization of foreign trade of plant protection products, and plant nutrition products, as well as has introduced few registers. In the area of pesticides were determined: the Register of Plant Protection Products, Register of Distributors and Importers of Plant Protection Products, and Register of Providers of the Services. Also, the Register of Plant Nutrition Products was determined. In addition, the registration of pesticides and fertilizers was modified to be in accordance with internationally recognized testing methods.